Electronic Word of Mouth (e-WoM) and Influencer Marketing Strategy on Purchase Decision of Skincare Products in Marketplace - Neng Nurniati; Citra Savitri; Syifa Pramudita Faddila (Yayasan Riset dan Pengembangan Intelektual, 2023)
In the digital era, online marketing strategies utilizing electronic word of mouth (e-Wom) and influencer marketing are increasingly popular and in high demand. Companies are now starting to use this marketing strategy to promote their products and services, which has a considerable impact. Consumers tend to trust the opinions and recommendations of people they follow on social media. This study aims to determine the effect of electronic word of mouth (eWom) and influencer marketing on purchasing decisions. The method in this research is a quantitative method with a descriptive verification approach. The population in this study were Generation Z women aged 13-25 years in Karawang Regency. The sample used was 100 respondents with the calculation of the Wibisono formula. The sampling technique used a nonprobability sampling method with a purposive sampling technique. Data analysis in this study used a structural equalition model (SEM) using SmartPLS. The results of this study indicate that the electronic word of mouth (eWom) variable has no direct relationship with the purchasing decision variable. Influencer marketing variables on purchasing decision variables show a positive and significant direct relationship.